What's missing from legal geography and materialist studies of law? Absence and the assembling of asylum appeal hearings in Europe. Issue 4 (19th August 2020) - Gill, Nick; Allsopp, Jennifer; Burridge, Andrew; Fisher, Dan; Griffiths, Melanie; Hambly, Jessica; Hoellerer, Nicole; Paszkiewicz, Natalia; Rotter, Rebecca
Abstract : There is an absence of absence in legal geography and materialist studies of the law. Drawing on a multi‐sited ethnography of European asylum appeal hearings, this paper illustrates the importance of absences for a fully‐fledged materiality of legal events. We show how absent materials impact hearings, that non‐attending participants profoundly influence them, and that even when participants are physically present, they are often simultaneously absent in other, psychological registers. In so doing we demonstrate the importance and productivity of thinking not only about law's omnipresence but also the absences that shape the way law is experienced and practised. We show that attending to the distribution of absence and presence at legal hearings is a way to critically engage with legal performance. Abstract : Legal geography and materialist studies of the law have not fully reckoned with absence. Drawing on a multi‐sited ethnography of European asylum appeal hearings, this paper illustrates the importance of absences for a fully‐fledged materiality of legal events. In so doing, we show that attending to absence offers an indispensable criticality with respect to legal performances.